Reference SLE Didactics Framework Proposal for Moroccan Middle School Teachers: Immunology as a Model - Elmazouni, Nourdine Benelhadi; Rihane, Abdeslam; Tridane, Malika; Belaaouad, Said (International Journal of Engineering Pedagogy (iJEP), 2018)
Abstract—Immunology, by the nature of its concept, is of considerable benefit for the translation of the objectives of health education and teaching of sciences of life and earth (SLE) namely, the formation of the scientific mind and the development of a scientific culture for the student. It is from this angle that a course in immunology has acquired its citizenship right in the Moroccan curriculum of the SLE of the 3rd year of middle school education. Having experienced a scientific revolution, immunology raises several didactic problems for teachers. Continuing training in SLE didactics applied to immunology could be considered as a tool for the professionalization of the teaching act. In this article, we have proposed a reference framework for SLE didactics modeled on immunology to be integrated into the continuous training of teachers. This framework includes a body of knowledge on various aspects related to the didactics of immunology. These include the historical-epistemological development of immunology, its status in the curriculum and representations of Moroccan students on the concept of immunity.